2004
DOI: 10.1172/jci200418195
|View full text |Cite
|
Sign up to set email alerts
|

Murine autoimmune hearing loss mediated by CD4+ T cells specific for inner ear peptides

Abstract: Autoimmune sensorineural hearing loss (ASNHL) is characterized typically by bilateral, rapidly progressive hearing loss that responds therapeutically to corticosteroid treatment. Despite its name, data implicating autoimmunity in the etiopathogenesis of ASNHL have been limited, and targeted self-antigens have not been identified. In the current study we show that the inner ear–specific proteins cochlin and β-tectorin are capable of targeting experimental autoimmune hearing loss (EAHL) in mice. Five weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 50 publications
1
36
0
3
Order By: Relevance
“…Cochlin has also been implicated in autoimmune hearing loss in humans (Boulassel et al 2001;Baek et al 2006) and in experimental immune-mediated hearing loss in mice (Solares et al 2004). Similarly, CTL2 has been implicated in autoimmune hearing loss (Zeitoun et al 2005) and experimental antibodymediated hearing loss (Nair et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cochlin has also been implicated in autoimmune hearing loss in humans (Boulassel et al 2001;Baek et al 2006) and in experimental immune-mediated hearing loss in mice (Solares et al 2004). Similarly, CTL2 has been implicated in autoimmune hearing loss (Zeitoun et al 2005) and experimental antibodymediated hearing loss (Nair et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…2 Baek et al 3 demonstrated that patients with AIED have higher frequencies of interferon (IFN)-g-producing T cells and higher serum antibody titers compared with both normal hearing control subjects and patients with noise-and/or age-related hearing loss. Many autoantigens have been implicated as possible causal antigens (Ags) in AIED: heat-shock protein 70, 4,5 collagen II, 6 cochlin 3,7 and, most recently, b-tubulin. [8][9][10][11][12][13] Yoo et al [9][10][11] demonstrated that 67 (59%) of 113 patients with Ménière's disease had antibodies to a 55-kDa protein b-tubulin in guinea-pig inner ear extract.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,14,15 Transfer studies indicate that Ag-specific CD4 + T cells with a T-helper type 1 (Th1)-like phenotype mediate the development of EAHL by showing significantly increased auditory brain stem thresholds after adoptive transfer of autoantigen-activated CD4 + T cells into naïve recipients. 7,8,16,17 Recently, accumulating evidence has suggested that regulatory T (Treg) cells have a critical role in maintaining peripheral homeostasis and establishing controlled immune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, antibodies against microbial pathogen and mammalian HSPs are present in healthy individuals as well as in various diseases, arguing against the significance of HSP antibodies in the serological diagnosis of AIED [18,19]. Other antigens of great potential include the cochlin protein, identified initially by Boulassel et al [12] as a candidate autoantigen for SNHL, myelin protein Po [15], choline transporter-like protein 2 [17] as well as b-tectorin [20,21]. The hypothesis of a pathogenic role for either cochlin or b-tectorin is supported by experimental induction of hearing loss following adoptive transfer of T cell lines specific for these proteins [21].…”
Section: Introductionmentioning
confidence: 99%